How to ensure full vaccination? The association of institutional delivery and timely postnatal care with childhood vaccination in a cross-sectional study in rural Bihar, India - Mareike Schön; Esther Heesemann; Cara Ebert; Malavika Subramanyam; Sebastian Vollmer; Sebastian Horn (Public Library of Science (PLoS), 2022)
Incomplete and absent doses in routine childhood vaccinations are of major concern. Health systems in low- and middle-income countries (LMIC), in particular, often struggle to enable full vaccination of children, which affects their immunity against communicable diseases. Data on child vaccination cards from a cross-sectional primary survey with 1,967 households were used to assess the vaccination status. The association of timely postnatal care (PNC) and the place of delivery with any-dose (at least one dose of each vaccine) and full vaccination of children between 10-20 months in Bihar, India, was investigated. Bivariate and multivariable logistic regression models were used. The vaccines included targeted tuberculosis, hepatitis B, polio, diphtheria/pertussis/tetanus (DPT) and measles. Moreover predictors for perinatal health care uptake were analysed by multivariable logistic regression. Of the 1,011 children with card verification, 47.9% were fully vaccinated. Timely PNC was positively associated with full vaccination (adjusted odds ratio (aOR) 1.48, 95% confidence interval (CI) 1.06-2.08) and with the administration of at least one dose (any-dose) of polio vaccine (aOR 3.37 95% CI 1.79-6.36), hepatitis B/pentavalent vaccine (aOR 2.11 95% CI 1.24-3.59), and DPT/pentavalent vaccine (aOR 2.29 95% CI 1.35-3.88). Additionally, delivery in a public health care facility was positively associated with at least one dose of hepatitis B/pentavalent vaccine administration (aOR 4.86 95% CI 2.97-7.95). Predictors for timely PNC were institutional delivery (public and private) (aOR 2.7 95% CI 1.96-3.72, aOR 2.38 95% CI 1.56-3.64), at least one ANC visit (aOR 1.59 95% CI 1.18-2.15), wealth quintile (Middle aOR 1.57 95% CI 1.02-2.41, Richer aOR 1.51 95% CI 1.01-2.25, Richest aOR 2.06 95% CI 1.28-3.31) and household size (aOR 0.95 95% CI 0.92-0.99). The findings indicate a correlation between childhood vaccination and timely postnatal care. Further, delivery in a public facility correlates with the administration of at least one dose of hepatitis B vaccine and thus impedes zero-dose vaccination. Increasing uptake of timely PNC, encouraging institutional delivery, and improving vaccination services before discharge of health facilities may lead to improved vaccination rates among children.